(untitled) (Research, Society and Development, 2022)
The aim of this study was to assess smoking impact on oral health-related quality of life (OHRQoL). A cross-sectional study was carried out with smokers and non-smokers patients scheduled at a Faculty of Dentistry in Brazil. Sociodemographic data were collected and oral problems impact on quality of life were assessed through “Oral Health Impact Profile-14” (OHIP-14) questionnaire. The World Health Organization criteria were used to assess dental caries and periodontal disease. Data analysis was performed by descriptive and inferential statistics. Two hundred and seven individuals participated in the study, 112 non-smokers and 95 smokers. Most smokers were males (54.25%), the average smoking time was 24.74 ± 14.84 years and 54.72% of them reported smoking more than 11 cigarettes/day. Smokers scored higher values in OHIP-14 (p = 0.026) and in dimensions “functional limitation” (p < 0.001), “psychological discomfort” (p = 0.024) and “psychological disability” (p = 0.047). In addition, smokers had higher percentages of sextants with periodontal pockets (p < 0.001) and moderate to advanced attachment loss (p = 0.029). In short, smokers suffered a greater impact on OHRQoL, in addition to a worse periodontal condition compared to non-smokers.